Temporal dynamics of immune-stromal cell interactions in fracture healing - Capobianco, Christina A.; Hankenson, Kurt D.; Knights, Alexander J. (Frontiers in Immunology, 2024)
Bone fracture repair is a complex, multi-step process that involves communication between immune and stromal cells to coordinate the repair and regeneration of damaged tissue. In the US, 10% of all bone fractures do not heal properly without intervention, resulting in non-union. Complications from non-union fractures are physically and financially debilitating. We now appreciate the important role that immune cells play in tissue repair, and the necessity of the inflammatory response in initiating healing after skeletal trauma. The temporal dynamics of immune and stromal cell populations have been well characterized across the stages of fracture healing. Recent studies have begun to untangle the intricate mechanisms driving the immune response during normal or atypical, delayed healing. Various in vivo models of fracture healing, including genetic knockouts, as well as in vitro models of the fracture callus, have been implemented to enable experimental manipulation of the heterogeneous cellular environment. The goals of this review are to: (1) summarize our current understanding of immune cell involvement in fracture healing;(2) describe state-of-the art approaches to study inflammatory cells in fracture healing, including computational and in vitro models; and (3) identify gaps in our knowledge concerning immune-stromal crosstalk during bone healing.